PEMBERIAN KONSELING GIZI TERHADAP STATUS GIZI DAN HASIL PEMERIKSAAN SPUTUM BTA PENDERITA TUBERKULOSIS PARU DI WILAYAH KERJA PUSKESMAS BITUNG BARAT KOTA BITUNG - Daniel Robert (Jurnal GIZIDO, 2013)
Since 1995 the WHO and the International Union of Tuberculosis and Lung Diseaseagains IUATLD) has recommended Tuberculosis Lung Disease Eradication programimplemented DOTS strategy (Directly Observed Treatment Shortcoursechemotherapy). Then developed along with the formation of GERDUNAS-TB(Tuberculosis Control National Integrated Movement of date March 24, 1999), theTuberculosis Lung Disease Eradication Programme Tuberculosis Control turned into.The World Bank states DOTS strategy proved to be economically coping strategies aremost effective (cost-effective). (Department of Health, 2005). Nutritional counseling is acommunication activities to inculcate and promote understanding, attitudes andbehavior so membantu patients recognize and address nutritional issues, requiringcareful assessment, appropriate nutrition intervention and can be properly monitored sothat the nutritional care can help the healing process of the disease (Persagi, 2010).This type of research is quasi-experimental (quasi-experimental) design Pre and posttestcontrol group design. Subjects were divided into an intervention group of patientsgiven nutritional counseling pulmonary TB and pulmonary TB control group of patientsnot given nutritional counseling, which is determined by purposive, as well as samplestotaling 44 people. Data analysis using Wilcoxon test using SPSS version 18.00. Theresults are there effects of nutrition counseling on nutrition status of patients withpulmonary TB (p = 0.024), no effect of nutritional counseling on sputum smeardiagnostic workup of patients with pulmonary TB (p = 0.000).